The latest geodynamics in Central Asia: primary and secondary mantle melting anomalies in the context of orogenesis, rifting, and lithospheric plate motions and interactions - I. S. Chuvashova; S. V. Rasskazov; Sun Yi-min (Геодинамика и тектонофизика)
A comprehensive model for deep dynamics in Asia has been developed from the data on the evolution of melting anomalies in the context of lithospheric plate motions, interactions, orogeny, and rifting. The key components of our model are the primary (transition layer) and secondary (upper mantle) melting anomalies (Gobi, Baikal, and North Transbaikalia; and Hangay, Sayan, and Vitim, respectively). It is inferred that the primary melting anomalies originated at the beginning of the latest geodynamic stage (ca. 90 Ma) as a result of the transition layer distortion by lower mantle flows. Such primary anomalies were caused by avalanche collapses of the slab material that had been stagnated under the closed fragments of the Solonker, Ural-Mongolian paleooceans and the Mongol-Okhotsk Bay of Paleopacific. The secondary melting anomalies occurred due to the Early-Middle Miocene structural reorganization in the Pacific-Asian and Indo-Asian interaction zones. The primary melting anomalies governed the spatial distribution of forces and processes of the latest geodynamic stage. The secondary melting anomalies resulted from the lithospheric motions relative to the primary anomalies and provided for the development of orogeny and rifting. The Baikal-Mongolian corridor of asthenospheric flows was limited by the lateral zones of convergent interactions between India and Asia in the southwest, and North America and Asia in the northeast. In these lateral zones, Late Phanerozoic paleoslabs and ascending mantle fluxes were revealed in the transition layer, as well as in the upper mantle, without any destruction by the asthenospheric flows.